Study of Gender-based In-Hospital Mortality Difference in Patients with Acute Myocardial Infarction (Bangladesh Heart Journal, 2018)
Background: In-hospital mortality in female patients with acute myocardial infarction (AMI) and factors affecting this may be different from those of their male counterpart. The aim of the current study was to compare the in-hospital mortality between female and male patients with AMI and to compare the differences in age, risk factors, treatment given and complications between them.Methods: Total 200 nonrandomised patients with a definite diagnosis of AMI admittedover a period of one year (January 2008 - December 2008) were enrolled in the study, in which 100 female patients were considered as cases and 100 male patients as controls. Both groups were studied prospectively.Datawere collected in prefixed questionnaire and data sheet and were analysed using SPSS software.Results: mean age of the female patients was significantly higher than that of their male counterpart (57.0±10.1 years and 53.3±10.3 years respectively, p=0.029). Diabetes mellitus and hyperlipidemia were significantly higher in females than those in males (39% vs 24%, p=0.022 and 45% vs 32%, p=0.040 respectively), while smoking was staggeringly higher among the males (59%) compared to the females (4%) (p0.05).Conclusion: Female patients with AMI had significantly higher in-hospital mortality. Early hospitalization and optimal treatment are crucial to decrease mortality in female patients.Bangladesh Heart Journal 2017; 32(2) : 119-124